.12-2x=9x+45

Simple and best practice solution for .12-2x=9x+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .12-2x=9x+45 equation:



.12-2x=9x+45
We move all terms to the left:
.12-2x-(9x+45)=0
We add all the numbers together, and all the variables
-2x-(9x+45)+0.12=0
We get rid of parentheses
-2x-9x-45+0.12=0
We add all the numbers together, and all the variables
-11x-44.88=0
We move all terms containing x to the left, all other terms to the right
-11x=44.88
x=44.88/-11
x=-4+0.88/11

See similar equations:

| x+32=2(x+20) | | j-2/11=8/11 | | 14=9-2x+11+8x | | 2x-11=-3x-6x | | 5x+10=2x+40x= | | 13-6v=37 | | 12x6=(10x6+(x6 | | 12+6x=3(−x+3)−42 | | (x+5)+(3x)=90 | | f(3)=1.50+2.00 | | 1/x+1/2x=1/12 | | 56=(6x=2) | | y+24+7y+44=180 | | f-9=15 | | 1/8(6p+20)=7 | | w-1/2=8 | | 12x-4=8-10x | | 8-(2y+9)=3(4y-5) | | (9x+6)-8x=4x | | 8-4x=-2x-6x | | 2(x-4)^2=-200 | | 3(x+4)=5x-2x+12 | | 12.27+0.8=c | | 23.42-s=15.42 | | 4x+3=3(x+1)-2x | | 12(6x+20)=-2x | | r+1/4=41/4 | | 4n=2+6n | | 12x+x3=14x+7 | | 4x+1+5x-1+4x+1+5x-1=144 | | 7(2y+3)=21+14y | | x²+4x+4=11 |

Equations solver categories